Year-round record of dissolved and particulate metals in surface snow at Dome Concordia (East Antarctica). (November 2015) - Grotti, Marco; Soggia, Francesco; Ardini, Francisco; Magi, Emanuele; Becagli, Silvia; Traversi, Rita; Udisti, Roberto
Highlights: Marine major elements and trace elements in snow are higher in winter than in summer. Partitioning between dissolved and particulate phases depends only on the element. The marine contribution of trace elements in inland snow is negligible. Cd, Cr, Cu, Pb and Zn in surface snow at Dome Concordia have a dominant anthropogenic origin. Abstract: From January to December 2010, surface snow samples were collected with monthly resolution at the Concordia station (75°06'S, 123°20'E), on the Antarctic plateau, and analysed for major and trace elements in both dissolved and particulate (i.e. insoluble particles, >0.45 μm) phase. Additional surface snow samples were collected with daily resolution, for the determination of sea-salt sodium and not-sea-salt calcium, in order to support the discussion on the seasonal variations of trace elements. Concentrations of alkaline and alkaline-earth elements were higher in winter (April–October) than in summer (November–March) by a factor of 1.2–3.3, in agreement with the higher concentration of sea-salt atmospheric particles reaching the Antarctic plateau during the winter. Similarly, trace elements were generally higher in winter by a factor of 1.2–1.5, whereas Al and Fe did not show any significant seasonal trend. Partitioning between dissolved and particulate phases did not change with the sampling period, but it depended only on the element: alkaline and alkaline-earth elements, as well as Co, Cu, Mn, Pb and Zn were for the most part (>80%) in the dissolved phase, whereas Al and Fe were mainly associated with the particulate phase (>80%) and Cd, Cr, V were nearly equally distributed between the phases. Finally, the estimated marine and crustal enrichment factors indicated that Cd, Cr, Cu, Pb and Zn have a dominant anthropogenic origin, with a possible contribution from the Concordia station activities.